BUSINESS POLICY AND STRATEGY / The Art of Competition - Babson Harold C.; Deusen Cheryl Van; Williamson Steven (Auerbach Publications, 2007)
INDUSTRIAL MANAGEMENT BUSINESS POLICY STRATEGY (SBLROJ[APLMJ ELRLMJVJ SRNLXLMJ X]P FSL[FLUJVF]P VXUAXJDLMJs